Pharmacokinetics of liposomal encapsulated buprenorphine suspension following subcutaneous administration to cats. Issue 3 (20th September 2016) - Johnson, R. J.; Kerr, C. L.; Enouri, S. S.; Modi, P.; Lascelles, B. D. X.; del Castillo, J. R. E.
Abstract : We investigated the effects of liposome encapsulation at prolonging the systemic exposure of buprenorphine following subcutaneous administration in cats. Seven healthy male cats were dosed intravenously with 0.02 mg/kg buprenorphine solution (STD‐BUP), followed 14 days later by a subcutaneous injection of 0.2 mg/kg buprenorphine as a liposomal suspension (SUS‐BUP) containing drug molecules both in liposomes and the suspending vehicle. Buprenorphine time plasma concentration data for both dosing routes were analyzed simultaneously with four compartmental models. Goodness of fit was assessed both graphically and with the Akaike information criterion. The time‐course of intravenous STD‐BUP was biphasic, with a 4.39 h average terminal half‐life. The subcutaneous SUS‐BUP produced plasma buprenorphine concentrations above 0.5 μg/L for more than 96 h, with three distinct peaks in the first 15 h. The model with best fit comprised a central and a peripheral compartment, plus three subcutaneous absorption compartments: one of dissolved drug molecules that were absorbed through a first‐order process, and two of liposome‐encapsulated drug molecules that were transferred to the solution compartment through separate zero‐order processes. Liposomes effectively prolonged the systemic exposure of buprenorphine in cats.